Einige Grenzwertsätze für additive zahlentheoretische Funktionen - Uždavinys, R. (Lithuanian Mathematical Journal, 1961)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Р. Уждавинис. Некоторые предельные теоремы для аддитивных арифметических функцийR. Uždavinys. Kai kurios adityvinių aritmetinių funkcijų ribinės teoremos